1982
DOI: 10.1159/000156063
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic Study of Cercopithecus pogonias grayi × Cercopithecus ascanius katangae Hybrids

Abstract: The G-banded karyotypes of a male and a female hybrid born of the cross between a Cercopithecus pogonias grayi (2 n = 72 XY) and a C. ascanius katangae (2 n = 66 XX) are reported. The constant chromosome number 2 n = 69 of both the male and female hybrids equals the arithmetic mean of the parental chromosome. A correlation between the hybrid karyotypes and those of their parents is proposed. The typical acro-centric autosomes of C. pogonias grayi are found again in the offspring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1989
1989
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 1 publication
0
3
0
Order By: Relevance
“…The strong skeletal similarities between Cercopithecus and Chlorocebus ultimately result from their similarity in body size and generalist adaptations, and are likely also due in part to their long history of hybridization (Aldrich-Blake, 1968;Detwiler, 2004Detwiler, , 2010Detwiler et al, 2005;Dugoujon et al, 1982;Sineo, 1990;Struhsaker et al, 1988;Tapanes, 2016). It is remarkable that even the unusually high variation in karyotype does not prevent these different species from hybridizing (Detwiler, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The strong skeletal similarities between Cercopithecus and Chlorocebus ultimately result from their similarity in body size and generalist adaptations, and are likely also due in part to their long history of hybridization (Aldrich-Blake, 1968;Detwiler, 2004Detwiler, , 2010Detwiler et al, 2005;Dugoujon et al, 1982;Sineo, 1990;Struhsaker et al, 1988;Tapanes, 2016). It is remarkable that even the unusually high variation in karyotype does not prevent these different species from hybridizing (Detwiler, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike their papionin and other anthropoid relatives, cercopithecins have considerable variation in chromosome number, with diploid numbers ranging from 48 to 72 (Chiarelli, 1968; Dutrillaux, 1988; Lo Bianco et al, 2017; Moulin et al, 2008; Sineo, 1990). Hybridization is known to occur across species with different chromosome numbers (Dugoujon et al, 1982; Sineo, 1990). After the recent publication of the Chlorocebus reference genome by Warren et al (2015), Svardal et al (2017) reported high levels of admixture between Chlorocebus species that diverged during the Late Pleistocene.…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid animals have been observed in the wild and in captivity between some taxa of Old World monkeys and gibbons, for example intergeneric hybrids between Papio × Macaca (Moore et al, 1999), Cercopithecus pogonias × Cercopithecus ascanius (Dugoujon et al, 1982), Symphalangus × Hylobates (Pellicciari et al, 1988). Among Prosimians, hybrids between species or subspecies were most commonly described in lemurs (Rumpler and Dutrillaux, 1976;Ratomponirina et al, 1982), for example Eulemur albocollaris × Eulemur fulvus rufus and Eulemur f. fulvus × Eulemur m. macaco.…”
mentioning
confidence: 99%